2001
DOI: 10.1104/pp.010333
|View full text |Cite
|
Sign up to set email alerts
|

Insertional Mutants of Chlamydomonas reinhardtii That Require Elevated CO2 for Survival

Abstract: Aquatic photosynthetic organisms live in quite variable conditions of CO 2 availability. To survive in limiting CO 2 conditions, Chlamydomonas reinhardtii and other microalgae show adaptive changes, such as induction of a CO 2 -concentrating mechanism, changes in cell organization, increased photorespiratory enzyme activity, induction of periplasmic carbonic anhydrase and specific polypeptides (mitochondrial carbonic anhydrases and putative chloroplast carrier proteins), and transient down-regulation in the sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 47 publications
(21 reference statements)
0
21
0
Order By: Relevance
“…CCP2 (low-CO 2 -inducible chloroplast envelope protein 2) and LCI1 (low-CO 2 -inducible membrane protein 1) were also strongly induced by increased light. As these genes are induced by low CO 2 (Burow et al, 1996;Van et al, 2001;Pollock et al, 2004), they have been proposed to be part of the inorganic carbon concentrating mechanism. High light may induce LCI1 because the resulting increase in the rate of photosynthesis leads to a temporary decrease in the internal CO 2 concentration, which induces genes involved in the carbon concentrating mechanism (McGinn et al, 2003;Spijkerman, 2011).…”
Section: Increase In Irradiance In the Nonsaturating Range Triggers Wmentioning
confidence: 99%
“…CCP2 (low-CO 2 -inducible chloroplast envelope protein 2) and LCI1 (low-CO 2 -inducible membrane protein 1) were also strongly induced by increased light. As these genes are induced by low CO 2 (Burow et al, 1996;Van et al, 2001;Pollock et al, 2004), they have been proposed to be part of the inorganic carbon concentrating mechanism. High light may induce LCI1 because the resulting increase in the rate of photosynthesis leads to a temporary decrease in the internal CO 2 concentration, which induces genes involved in the carbon concentrating mechanism (McGinn et al, 2003;Spijkerman, 2011).…”
Section: Increase In Irradiance In the Nonsaturating Range Triggers Wmentioning
confidence: 99%
“…Although initially identified as a probable Ci transport mutant, a recent study reported that the expression profiles of several CO 2 responsive genes in pmp1 differ from those in wild type and suggested that the Pmp1 gene product might regulate the expression of Ci transporter genes (14). Another recent observation regarding pmp1 is its unusual, air-dieing phenotype (15,16): it grows well in either high (5%) or very low (Ͻ200 ppm) CO 2 , but dies in low (air-level) CO 2 (350-450 ppm). This conspicuous phenotype distinguishes pmp1 from most other high CO 2 -requiring mutants and indicates the existence of multiple Ci transport systems in C. reinhardtii corresponding to multiple, CO 2 level-dependent acclimation states.…”
mentioning
confidence: 99%
“…Screening DNA insertional mutagenesis libraries in C. reinhardtii has become a popular strategy for identifying important genes involved in specific cellular pathways and processes (Debuchy et al, 1989;Rochaix, 1995;Tam and Lefebvre, 1995;Niyogi et al, 1997;Adam and Loppes, 1998;Davies et al, 1999;Moseley et al, 2000; Van et al, 2001;Dame et al, 2002;Polle et al, 2003). Our screening efforts resulted in the identification of several mutants that were compromised in their ability to photoproduce H 2 .…”
Section: Introductionmentioning
confidence: 99%